PEACEFUL LOCAL ELECTION, PEACEFUL INDONESIA - Agus Raharjo (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Simultaneous Local Elections (Pilkada) of the second phase will start soon. Stages of the campaign is not yet started, but the tricks and intrigue,strategies and programs race, had begun even before the start flag hoisted. The indication of this simultaneous local elections of the second phase is more crowded, have started to appear on the action of campaign team and supporters......